Experimental study on the effects of ghrelin on gastric smooth muscle and posterior limb skeletal muscle in mice - Wang, Ping; Yu, Cunbo; Li, Yibing; Zhang, Xiaoxiao; Yao, Xueli; Zhang, Yingjian (Frontiers in Medicine, 2025)
IntroductionThis study aims to systematically explore the regulatory effects of ghrelin on hindlimb skeletal muscle function and gastrointestinal smooth muscle in mice. The objective is to elucidate the improvement effects of ghrelin on functional constipation through regulating skeletal muscle function and gastrointestinal motility, providing new theoretical support for the prevention and treatment of functional constipation.MethodsDexamethasone-induced in vitro cell models and tail suspension-induced in vivo mouse models were employed to analyze the regulatory effect of ghrelin on the PI3K-Akt-mTORC1 signaling pathway. Additionally, a loperamide-induced constipation mouse model was used to evaluate the effects of ghrelin on fecal output, gastric motility, and smooth muscle activity. Experimental techniques included Western blotting, enzyme-linked immunosorbent assay (ELISA), histopathological staining, phenol red assay, and quantitative analyses of Ca2+ and ATP to comprehensively assess the impact of ghrelin on muscle atrophy and gastrointestinal function.ResultsThe results showed that, in vitro, ghrelin significantly upregulated the expression of p-AKT and reduced the levels of p-Foxo3a, effectively alleviating muscle atrophy. In vivo, the muscle condition of mice was improved and the expression of atrophy-related proteins (MAFbx and MuRF1) decreased, promoting the functional recovery of hindlimb muscles. In constipated mice, ghrelin increased fecal water content and defecation frequency, and accelerated gastric emptying, findings consistent with elevated ghrelin levels in serum and tissue. Moreover, ghrelin promoted calcium ion influx and ATP production in gastric smooth muscle cells, thereby enhancing gastrointestinal motility.DiscussionIn conclusion, ghrelin effectively alleviates muscle atrophy by activating the PI3K-Akt-mTORC1 signaling pathway, and improves gastrointestinal motility by enhancing smooth muscle activity. These findings highlight ghrelin’s potential as an effective therapy for functional constipation.